Late intraprosthetic dislocation of a monoblock dual-mobility cup cemented into a well-fixed cementless acetabular shell. A case report - Ulgelmo, Maurizio; Sandri, Andrea; Regis, Dario; Casablanca, Edoardo; Toso, Giovanna; Valentini, Roberto; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2022)
Intraprosthetic dislocation (IPD) is a specific implant-related complication of dual mobility (DM) implants, which is defined as a dissociation of polyethylene (PE) liner from the femoral head.We report a unique case of  late IPD of a monoblock DM cup cemented into a well-fixed cementless acetabular shell for recurrent dislocation of total hip arthroplasty (THA). A 77-year-old woman was admitted to our department for acute right hip pain, functional impairment and inability to bear weight without any trauma. Three years earlier, she underwent revision THA for recurrent dislocation with a monoblock DM cup cemented into a well-fixed cementless acetabular shell according to the “double-socket” technique. Three months after that revision the patient experienced an anterior THA dislocation, which was managed by closed reduction under sedation in the emergency room. No additional episodes of prosthesis instability occurred.Upon admission, radiographic evaluation showed  right THA dislocation. X-rays performed  after closed reduction revealed eccentric positioning of the head inside the cup, and a direct contact between the metal head and the cup was revealed by subsequent CT scan, confirming the suspicion of IPD. The patient underwent revision surgery, during which the PE liner was found lodged within the cup in a subluxated position, disassembled from the inner head. Both the acetabular cup and modular femoral stem proved well-fixed and impossible to remove, therefore they were retained. The explanted DM components were replaced with new ones of the same size and, thanks to the femoral neck's modular nature, it was substituted with a longer one, which resulted in improved stability against intraoperative stress maneuvers. The postoperative course was uncomplicated. At 1-year follow-up, the patient had a good functional recovery.